Progression of cognitive impairment in Parkinson’s disease correlates with uric acid concentration - Zhai, Rui-Xue; Yu, Hui; Ma, Han; Liu, Ting-Ting; Zhong, Ping (Frontiers in Neurology, 2024)
This study assessed the relationship between the progression of Parkinson's disease (PD) with cognitive impairment and changes in serum uric acid (UA) and homocysteine (Hcy) concentrations and explored the factors influencing PD with cognitive impairment.The study randomly selected 74 patients with PD and evaluated their cognitive function using the Montreal Cognitive Assessment Scale (MoCA). Patients with PD were divided into two subgroups: those with and without cognitive impairment. PD severity was evaluated and graded using the Hoehn and Yahr (H-Y) scale. Another 60 middle-aged and older individuals without PD during the same period were selected as a control group. Blood UA and Hcy concentrations in each group were measured to assess the relationship between PD, cognitive impairment, and changes in UA and Hcy concentrations.The PD group with cognitive impairment had a lower UA concentration and higher Hcy concentration. The UA concentration was significantly higher in the early PD stages than in the middle and late stages (P<0.05). A significant negative relationship between MoCA scores and serum UA levels was found in patients with PD, whereas a positive relationship existed between MoCA scores and serum Hcy concentrations. Regression analysis showed that a higher UA concentration was an independent protective factor for PD with cognitive impairment, while a higher Hcy concentration was a risk factor (P<0.05). A serum UA concentration of 212.9 mmol/L and Hcy concentration of 13.35 mmol/L could distinguish between patients with PD with or without cognitive impairment with a sensitivity of 93.2% and specificity of 43.3%.PD and cognitive impairment were associated with a decrease in UA concentration; the later the H-Y stage was, the lower the UA concentration was. The increase in Hcy concentration was related to PD and its cognitive impairment, whereas it is not significantly correlated with PD progression.